Influence of Forensic Accounting on Litigation Support and Engagement in Nigeria - Osunwole, Olatunji Oludayo; Adewumi, Ademola, Adeniran; Adeyemi, Olatoke Adewale; Adekanye, Taiwo (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
The research focused on the influence of forensic accounting on the objectivity of forensic accountant’s investigation and the Attorney’s judgment in litigation cases in Nigeria. The study was carried out using a descriptive survey design. The study population is the over 400 professionals and practitioners in Osogbo, Osun State which included deposit money banks, law firms, audit firms, higher education institutions as well as small and mid-sized industries. In determining the sample size, Solvin’s formula was used and 200 respondents were selected in the study while a technique of randomization and convenience sampling has been applied. For this study, primary data were used. Questionnaires have been employed as a tool for collecting data. The results of the study showed that forensic accounting (α = 0.293; p < 0.05) and (α = 0.243; p < 0.05) had positive and significant effect on the objectivity of forensic accountant’s investigation and the Attorney’s judgment in litigation cases in Nigeria respectively. The study concluded that the use of forensic accounting services in Nigeria is an effective way to obtain verifiable evidence and support for litigation that aids activities of Attorney’s in the process of prosecuting fraudsters and ensuring dispute resolution. The study recommends that management of firms in Nigeria should develop more interest in forensic accounting by recruiting more forensic accountants with good knowledge in investigative skills and litigation support services as part of their accounts and audit departments.